TOWARDS AN ECONOMIC THEORY OF THE LIMITS OF INSURABILITY - Gollier, Christian (Assurances, 2001)
ln an Arrow-Debreu economy, all risks are shared efficiently at equilibrium. This result is in contradiction with the fact that many risks are not insured, and that others are covered only through a non-market system. This is the case for many risks associated to environment, technology, human capital. ln this paper, we review the different arguments that have been developed during the last twenty years by economists to explain the limits of insurability by competitive markets. In addition to transactions costs, adverse selection and (ex ante and ex post) moral hazard, we examine arguments based on the size of losses, on low probabilities, on limited liability, on ambiguity and on some dynamic aspects of risk management.